DIPLOMASI MARATON INDONESIA TERHADAP ISU RAKHINE STATE - Simanjuntak, Triesanto Romulo (Department of International Relations Universitas Satya Negara Indonesia, 2023)
The conflict in Myanmar was triggered by discrimination against one of the ethnic minorities, namely the Rohingya living in Rakhine State. In 2017, the conflict in Rakhine State broke out again when a military operation carried out by the Myanmar military attacked the Arakan Rohingya Salvation Army (ARSA), one of the armed militia groups in Rakhine State. This military operation caused the Rohingya ethnic in Rakhine State to become victims. The Indonesian government made a quick move by performing marathon diplomacy. One of the implementations of marathon diplomacy carried out by the Indonesian government is to directly visit Myanmar and meet with several Myanmar authorities who are responsible for the incident. The Indonesian government also went to Bangladesh, visiting the Rohingya refugee sites with the largest number of refugees. This Indonesian marathon diplomacy approach bore fruit because the Indonesian delegates were later well welcomed by the government of Myanmar and Indonesia also received support from the United Nations (UN) and other countries for its humanitarian action in Myanmar.